High-Performance Mimo Ofdm Wireless Systems With Generalized Prefix - Yıldız, Hakan; Cooklev, Todor; Doğan, Hakan; ACAR, YUSUF (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2013)
Consumers require increasing data rates and therefore it is important to develop techniques that increase the spectrum efficiency. MIMO OFDM is a fundamental technology for high data rate wireless systems. Correlation among the different spatial streams is the main factor limiting the spectral efficiency. All practical MIMO OFDM wireless systems use cyclic prefix (CP). In this paper we propose a novel prefix for MIMO OFDM wireless systems, referred to as generalized prefix. This generalized prefix provides additional degree of freedom, which can be optimized and provides improved performance for correlated MIMO channels.
Keywords: Generalized Prefix; OFDM; MIMO; Fading